"Put the blame on…others!": The battle of cyclists against pedestrians and car drivers at the urban environment. A cyclists' perception study. (August 2016) - Paschalidis, Evangelos; Basbas, Socrates; Politis, Ioannis; Prodromou, Mixalis
Highlights: Research hypothesis: cyclists blame themselves for accidents with pedestrian and driver for car accidents. Undertaken research: direct questionnaire survey to cyclists at a shared-use recreational path. Research tools: two linear regression models; perceived responsibility as dependent variable. Main findings: cyclists with car accessibility differ compare to those without car. Abstract: The main hypothesis of the paper is that cyclists tend to blame primarily car drivers, for the conflict events they have experienced with cars, but they do not have the same intention for the conflict events with pedestrians. For this purpose, 306 cyclists were interviewed through a revealed questionnaire survey and 64% revealed that they had experienced a conflict with a pedestrian whereas 55% revealed that they had experienced a conflict with a car. From the responses, two linear regression models were developed, with the perceived responsibility considered as the dependent variable. The cycling–pedestrian model indicated that cyclists who also have car accessibility, tend to blame primarily the pedestrians for the incidents, compared to cyclists who do not possess a car. Further, cyclists tend to give less responsibility to pedestrians for incidents occurred at sidewalks, crosswalks, etc. compare to incidents occurred at shared use paths. In addition, cyclists do not blame pedestrians for conflicts occurred primarily at sidewalks and crosswalks; places were pedestrians are considered to have the priority. Finally, cyclists aged between 55 and 64 years old, are giving less responsibility to pedestrians for the incident, compare to cyclists aged between 25 and 39 years old. On the other hand, the cycling–car model showed that an illegal cyclist's movement at a road segment can reduce by half the responsibility the cyclists give to the car drivers, compare to the responsibility they give when the latter have an aggressive driving behavior. It was also found that cyclists, who tend to cycle less than 1 h, do not blame so much the car drivers for the incident, compared to cyclists that cycle for longer. Finally, cyclists who prefer the bicycle lane to be located along the road instead at the sidewalk, tend to accuse less the drivers for the incident.